2020
DOI: 10.18231/j.sujhs.2019.015
|View full text |Cite
|
Sign up to set email alerts
|

A study of foramen magnum and its clinical relevance

Abstract: Introduction: Foramen magnum is very important land mark as it is closely related with brainstem and spinal cord. Morphometric parameters of foramen magnum are required for forensic investigations & anthropological identification of unknown individual. As there is paucity of literature regarding variations in size & shape in reference to different races which prompted us for this study. Aims and Objective: The aim was to study the morphology of foramen magnum that can be applied for many invasive surgical as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
2
1
0
Order By: Relevance
“…As our study demonstrates, the foramen magnum's most prevalent shapes were oval and round, mirroring the results of previous research (Garcia et al, 2011). Similarly, the occipital condyle shapes noted in our sample -kidney, oval, 8-like, S-like, ring-like, and triangularalign with the shapes identified in other studies (Kumar et al, 2019) (Ozer et al, 2011), though there was a discrepancy in the most common shape, with our study identifying the kidney shape as the most common, in contrast to the oval-like shape identified by Ozer et al…”
Section: Discussionsupporting
confidence: 87%
“…As our study demonstrates, the foramen magnum's most prevalent shapes were oval and round, mirroring the results of previous research (Garcia et al, 2011). Similarly, the occipital condyle shapes noted in our sample -kidney, oval, 8-like, S-like, ring-like, and triangularalign with the shapes identified in other studies (Kumar et al, 2019) (Ozer et al, 2011), though there was a discrepancy in the most common shape, with our study identifying the kidney shape as the most common, in contrast to the oval-like shape identified by Ozer et al…”
Section: Discussionsupporting
confidence: 87%
“…Shifankandey et al found mostly oval or circular FM in their study, which is similar to our study [9]. Arjun Kumar et al along with the normal shapes found diamondshaped FM in their study [10].…”
Section: Shape Of Foramen Magnumsupporting
confidence: 91%
“…Amit Singh Bharati et al found that AP diameter mean was 30 mm, SD 2.35 mm, the range was 24-37 mm, the TD mean was 26.1 mm, SD 2.13 mm 1, the range was 23-29 mm, FM index mean was 87.332 mm, SD 8.20 range was 75-100 mm,[5] and these readings were lesser than the readings in our study.Rajanisingh et al noted in their study that the AP diameter mean was 33.8 mm, SD 2.5 mm, mode was 34 mm, median was35 mm, TD mean was 28.2 mm, SD 2.6 mm, mode was 28 mm median was 30 mm, FM index mean was 1.21 mm, SD 0.11 mm[6], and comparatively these readings were similar to our study. Arjun Kumar et al found that AP diameter mean was 34.08 mm, SD2.25 mm, the range was 32.25-36.25 mm, TD mean was 28.17 mm, SD 2.85 mm, the range of 25.75-30.75 mm, p-value of APD<0.001 mm, p-value of TD<0.0 mm[10].FM index was calculated in our study; the mean was 1.23414 mm, SD was 0.095318 mm, these readings were similar to Sanjuktasahoo et al,Rajanisingh et al, and Sanjaykumarrevankar et al…”
mentioning
confidence: 98%